HJEM UDEN BØRN - Tjørnhøj-Thomsen, Tine (Tidsskriftet Antropologi, 2009)
This article explores how childless men and women in Denmark connect their longings for children and their purchase of a house with notions of home and kinship. It investigates thereby how their stories about hopes and longings for children stage and confi gure relationships between materiality and sociality. I draw primarily upon an ethnographic study of interfi le men and women in Denmark in the late nineties and their encounter with procreative technologies. The fi eldwork was centred on three local groups of the National Association for Involuntary Childless. Taking part in their meetings and social gatherings over a period of two years gave me an opportunity to obtain insights in how infertility affected and challenged their lives and plans, and it opened a window to a multi-faceted understanding of kinship in Denmark. This article thus focuses on the material dimensions of kinship and relatedness from a childless perspective. The childless people are in a particular empirical position because what they think and say about children and family life exists primarily as hopes, longings and future projections. The aspirations for children nevertheless contain things and materiality and they epitomize how physicality, locality, dwelling, things and consumer goods are part and parcel of kinship thinking. Keywords: Kinship, involuntary childlessness, things, house/home.